Determination of Antioxidant Capacities of Phlomis pungens Wild. var. hispida Hub.-Mor. - Keser, Serhat; Turkoglu, Semra; Celik, Sait; Turkoglu, Ismail (Asian Journal of Chemistry, 2012)
The genus Phlomis L. belongs to the Lamiaceae family and encompasses 100 species native to Turkey, North Africa, Europe and Asia. It is a popular herbal tea enjoyed for its taste and aroma. Phlomis species are used to treat various conditions such as diabetes, gastric ulcer, hemorrhoids, inflammation and wounds. In this study, ethanol and water extracts were prepared from powdered P pungens flowers and leaves. Antioxidant activities were measured by 2,2-azino-bis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS(center dot+)) radical scavenging, 1,1-diphenyl-2-picryl-hydrazyl free radical (DPPH center dot) scavenging, superoxide anion (02) radical scavenging, reducing activity and ferrous metal chelating activity assays. In conclusion, P. pungens flowers and leaves had effective ABTS(center dot+) and DPPH center dot radical scavenging, superoxide anion radical scavenging, reducing power and metal chelating activities when compared with BHA, BHT and alpha-tocopherol as reference antioxidants.
Keywords: Phlomis pungens; Antioxidant capacity; DPPH center dot; ABTS(center dot+); Superoxide radical